ANALISIS KONSEP GURU PENGGERAK: PANDANGAN KI HAJAR DEWANTARA - Handara Tri Elitasari (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2022)
The 21st century changes influenced the education system in Indonesia. One of the changes was the implementation of mover teacher program in early 2021 which is expected to make educational changes. The mover teacher aims to maximize learning activities for students in an innovative and creative with educational technology to achieve educational goals. The learning presented must provide comfort to students to increase the motivation of learning. The purpose of writing this article was to analyze the relationship between the concept of mover teacher in Ki Hajar Dewantara’s view. In this article, author used literature study by reviewing books and journals related to the mover teacher and the educational principles of Ki Hajar Dewantara. The results of the analysis showed that the concept of the mover teacher was unification of Ki Hajar Dewantara’s three educational principels which include ing ngarsa sang tuladha, ing madya mangun karsa, dan tut wuri handayani. The mover teacher as a learning facilitator helped students to learning activities in class. So it can be concluded that the relationship between the concept mover teacher with Ki Hajar Dewantara’s education principle. Keywords: mover teacher, Ki Hajar Dewantara